Por que as empresas fecham o capital no Brasil? - Padilha, Marco Tulio Clivati (2014)
Based on a sample of 119 companies that voluntarily delisted between 1999-2013, we investigated agency problems and access to capital as possible determinants to the delisting, controlling for cost to maintain the company listed, undervaluation, size, and stock liquidity. Proxies related to agency problems, such as higher ownership concentration, combined to lower return on assets, have strong influence on the stock delisting, as well as free cash flow and dividend payout. Regarding the use of capital markets to access follow on, as well as access to debt, we find that companies that delisted have less need to access the debt market, controlling for companies with the same profile. To the matter of control, we do not find evidence that cost to maintain the company listed nor the liquidity are determinant.